Caracterização hidrodinâmica, morfológica e sedimentológica do furo do rio maguari (Belém-Pará) - COSTA, Maurício da Silva da (2019)
Maguari Furo River, located further north of the city of Belém, is a river system influenced by the tide and possibly caused by a tectonic fault, exemplified by its form (NW-SE), and also reflects the influences of both Pará River as the bays of St. Anthony and Guajará. The field work was conducted on days 13/07, 09/09 and 27/11, 2010 between the dry and early rainy season, to characterize the hydrological/hydrodynamic, morphological and sedimentological processes, with the aid of a small boat fishing, a probe Condutctivity-and-Temperature-Depth (CTD), bottom sampler, an echosounder, current meters and an online data INMET. The weather presented abnormally close to the climatological normal, with average annual rainfall above average, with remnants of the performance of El Niño and the beginning of La Niña. The current followed the line of bore and presenting variations of direction and intensity according to the fluctuations of the tide and the morphology of the channel. The wind had to be inversely proportional to current, more intense in the afternoon, caused mainly by movements of air masses. Maguari Furo River shown the type dominated by tide is also classified as being of mesotidal. The salinity of the river in the Furo Maguari showed an abnormal pattern, with higher salinities at low tide, and having in general that the majority of profiles showing homogeneity with many low salinities due to the large volume of rainfall in previous months. According to the stratification of salinity showed almost homogeneous throughout the water column and can be classified as well mixed. The water temperature showed minimal variation both spatially and in time, showing no stratification. Maguari Furo River emerged possibly due to a fault, requiring geophysical data for their verification, characterized by a significant channel and displaying a gentle declivity between its downstream portion of the amount. And according to the analysis of sediments from Maguari Furo River classified as silt and sandy silt, with an extensive tidal flat and hydrodynamics of a high to very high.